THE ROLE OF HUMAN RESOURCE MANAGEMENT IN RETAINING TALENT: EMPIRICAL ANALYSIS OF YOUTH IN THE REPUBLIC OF NORTH MACEDONIA - Ristovska, Andrijana; Eftimov, Lјupcho (The Slovenian Academy of Management, 2019)
This paper studies the “brain drain” phenomenon through the prism of its intensity in the Republic of North Macedonia, and examines its positive and negative impacts, and its effect on the development of human resource management in the country, which is one of the key departments of any organization. This research, which covered 1400 respondents from a target group of young people, aged between 15 and 29, begins by providing answers to questions about the extent to which this phenomenon is present in Macedonia, the characteristics of the people who tend to leave the country, the pull factors that attract them to go abroad and the push factors that stimulate them to leave their own country, and the impact of human resource departments on the retention of staff and on recruiting staff back to the country, analyzed on the basis of an additional survey conducted among 10 human resource managers in large Macedonian companies. The Republic of North Macedonia is threatened by serious losses from brain drain that could decrease the human capital of the country and its economic growth. Furthermore, companies’ HR department policies about retaining, recruiting, and repatriation of staff and attracting new employees in the economy are underdeveloped and hugely influenced by heavy economic and political factors within the country.
Keywords: brain circulation, brain drain, brain gain, HRM, intellectual capital, migrations